(untitled) (World Economics and Finance Bulletin, 2024)
Achieving profit is one of the main goals that represent the success of banks and the continuation of competition with other banks in the competitive market. It is also one of the important aspects in making investment decisions by investors, as it represents the percentage of measuring the bank’s performance in the market. The quality and efficiency of management are also measured through profitability, as it is considered one of the most important factors that indicate the success of management. Therefore, this research aims to measure and evaluate the profitability of banks according to accounting indicators (ROA) (ROE) for the period from (2014 to 2023) and measure their future predictions through quantitative and statistical methods for the period from (2024-2033) for a sample of banks listed on the Iraqi Stock Exchange, which were represented by five banks: (Bank of Baghdad, Gulf Commercial Bank, Investment Bank of Iraq, National Bank of Iraq, and Trans Iraq Bank